2014
DOI: 10.3389/fmicb.2014.00229
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic chytrids sustain zooplankton growth during inedible algal bloom

Abstract: This study assesses the quantitative impact of parasitic chytrids on the planktonic food web of two contrasting freshwater lakes during different algal bloom situations. Carbon-based food web models were used to investigate the effects of chytrids during the spring diatom bloom in Lake Pavin (oligo-mesotrophic) and the autumn cyanobacteria bloom in Lake Aydat (eutrophic). Linear inverse modeling was employed to estimate undetermined flows in both lakes. The Monte Carlo Markov chain linear inverse modeling proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 117 publications
(169 reference statements)
3
41
1
Order By: Relevance
“…If more than four zoospores were produced per sporangium, as seen in multiple previous laboratory and field studies (38)(39)(40), then this suggests either that zoospores must obtain additional carbon from other sources besides the host or that the zoospores contain less than 10.7 pg carbon per cell, resulting in a lower carbon transfer efficiency. However, during blooms of large, inedible phytoplankton in French lakes, parasitism by chytrids and the subsequent production of zoospores was estimated to shunt ϳ20% of the total primary production into a form edible to zooplankton (18). Additionally, models that included parasitic chytrids showed an increase in carbon transfer efficiency and higher grazing efficiency than in a system lacking parasitic chytrids (41).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If more than four zoospores were produced per sporangium, as seen in multiple previous laboratory and field studies (38)(39)(40), then this suggests either that zoospores must obtain additional carbon from other sources besides the host or that the zoospores contain less than 10.7 pg carbon per cell, resulting in a lower carbon transfer efficiency. However, during blooms of large, inedible phytoplankton in French lakes, parasitism by chytrids and the subsequent production of zoospores was estimated to shunt ϳ20% of the total primary production into a form edible to zooplankton (18). Additionally, models that included parasitic chytrids showed an increase in carbon transfer efficiency and higher grazing efficiency than in a system lacking parasitic chytrids (41).…”
Section: Discussionmentioning
confidence: 99%
“…Zoospores were not only detected upstream from BAT, in the river, but also downstream, in the estuary and its lateral bays, potentially providing a previously unknown source of labile carbon to support estuarine food webs. The input of zoospores to the river and estuary may not be a trivial food source, since it has been shown that zoospores contribute to the mesozooplankton diet and can constitute up to 50 to 57% of the microzooplankton diet in French lakes (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This peak has been shown to exhibit a variable intensity depending on the season and year: it is sharper in spring and early summer and has been shown to be related to algal blooms [50,51]. Diatom frustules were predominant at these depths for the five sampling campaigns and contributed to massive precipitation of silica in the lake.…”
Section: Mineral Phases In the Superficial Zone Of The Lake (0-30-m Dmentioning
confidence: 96%
“…For example, in laboratory experiments, a diet of zoospores has been shown to improve the fitness and survival of the zooplankter Daphnia, compared to a diet of large colonial host diatoms (9). The potential importance of chytrids in aquatic food webs has been reviewed at length (3,(10)(11)(12)(13)(14)(15); however, understanding of the role that chytrid zoospores play in food web dynamics is limited by the lack of robust methods to quantify parasitic zoosporic fungi in water samples and in the guts of consumers.…”
mentioning
confidence: 99%